Cover Picture: Macromol. Mater. Eng. 1/2014. Issue 1 (January 2014) - Nuzzo, Anna; Coiai, Serena; Carroccio, Sabrina C.; Dintcheva, Nadka Tz.; Gambarotti, Cristian; Filippone, Giovanni
<x xml:space="preserve">Abstract</x> Cover: Small amounts of organoclay are added to a PLA/PA11 blend at 70% wt. of PLA to turn the drop‐matrix morphology into a co‐continuous one. In such a way, a remarkable improvement of the high‐temperature creep resistance is achieved owing to the clay‐rich PA11 framework, which interpenetrates the PLA and contributes to bear stresses up to 160 °C. Further details can be found in the article by A. Nuzzo, S. Coiai, S. C. Carroccio, N. T. Dintcheva, C. Gambarotti, and G. Filippone on page 31. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>